2002
DOI: 10.1021/jm010543z
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Helical Structure of Y2-Selective Analogues of Neuropeptide Y by Lactam Bridges

Abstract: The importance of helical structure in an analogue of NPY selective for the Y2 receptor, Ac[Leu28,31]NPY24-36, has been investigated by introducing a lactam bridge between positions 28 and 32. The resulting analogue, Ac-cyclo28/32[Ala24,Lys28,Leu31,Glu32]NPY24-36, is a potent Y2-selective agonist. Structural analysis by NMR shows that this analogue forms a helical structure in a 40% trifluoroethanol/water mixture, whereas in water only the region around the lactam bridge (Lys28-Glu32) adopts helical-like struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…157,158 Lactam bridges were introduced into the peptide fragments at various positions, with differing lengths (Lys/Glu or Orn/Asp), and different positions of the amide linkage (CO/NH or NH/ CO). Of these analogs, Ac-cyclo28/32[Lys28, Glu32]NPY24-36 was found to have the greatest Y 2 affinity; 157 its in-solution structure was determined by NMR, [159][160][161] and it was found to act as a Y 2 agonist. 162 It was postulated that the central amino acids play purely structural (rather than functional) roles, and the alanine scan showed that they were non-essential for binding to the Y 1 receptor.…”
Section: Peptidic Y 2 Receptor Ligandsmentioning
confidence: 99%
“…157,158 Lactam bridges were introduced into the peptide fragments at various positions, with differing lengths (Lys/Glu or Orn/Asp), and different positions of the amide linkage (CO/NH or NH/ CO). Of these analogs, Ac-cyclo28/32[Lys28, Glu32]NPY24-36 was found to have the greatest Y 2 affinity; 157 its in-solution structure was determined by NMR, [159][160][161] and it was found to act as a Y 2 agonist. 162 It was postulated that the central amino acids play purely structural (rather than functional) roles, and the alanine scan showed that they were non-essential for binding to the Y 1 receptor.…”
Section: Peptidic Y 2 Receptor Ligandsmentioning
confidence: 99%
“…NMR solution structures are also available for all three peptides. The C-terminal helical region of NPY is responsible for biological activity. , Mimetics of the neuropeptide Y helical region are potent antagonists of NPY, and exhibit anti-hypertensive and neuromodulatory activity. An example is the helix in the cyclic NPY analogue 87 , Ac[A24,K28,L31, E32]NPY(24−36), its helical structure being stabilized by a lactam bridge …”
Section: 36 Neuropeptide Y Peptide Yy and Pancreatic Polypeptidementioning
confidence: 99%
“…[61] Other authors have investigated mutants of truncated or cyclized versions of NPY. [62][63][64][65][66] Keire et al also estimated from CD and NMR spectra the helical content of PYY and the highly Y2-subtype-specific PYY fragment PYY . [67] The calculated helicity for PYY is 42 % and for PYY(3-36) is only 23 %, a result showing that the removal of two N-terminal amino acids resulted in major conformational alterations in solution; this observation was confirmed by our own dynamics data on PYY(3-36) (see below).…”
Section: The Solution Structures Of Peptides From the Npy Familymentioning
confidence: 99%